THERMAL RECONSTRUCTION BEHAVIOR OF MG-DOPED HYDROXYAPATITE POWDER DURING REHEATING AT 1000? - Evan Faadihillah Yozval, Abel
Hydroxyapatite is one of calcium phosphate variants that forms about 65-70 wt% of bone, and 70-80 wt% of teeth, this results on hydroxyapatite emergence as one of the most appealing bone graft materials. Hydroxyapatite has a thermal reconstruction behavior, in which, hydroxyapatite will reconstitute after transforming to other phases when reheated. This research goals mainly revolves around the observation thermal reconstruction of Mg-doped hydroxyapatite using two heating paths. The first heating path involves single heating at 1000?, and the second heating path involves consecutive heating at 1500? then reheating at 1000?. As-precipitated variants of the specimen produced HA phase, single heating variants produced HA + ?-TCP, and consecutive heating variants produced HA + ?-TCP phase after heating at 1500? and produced HA + ?-TCP after reheating at 1000?, In this research, phase transformation happened once when single heating is done, and twice when consecutive heating is done. The crystallinity of the specimen is also affected by heating and dopant composition variation, where crystallinity increase as the heating temperature rise, and decrease as the dopant composition rise.